ANALISIS NILAI TAMBAH IKAN ROA MENJADI SAMBAL PADA INDUSTRI SAL-HAN DIKOTA PALU - Pratama, Moh Riski; Damayanti, Lien; Kalaba, Yulianti (AGROTEKBIS, 2019)
This research aims to  find out the added value of Roa fish business become sauce at Sal-Han industry in Palu. The research was conducted on April 2017. Respondens were 5 employee and 1 leader selected. So that total respondens are 6 people. The research used primary and secondary data which were analyzed using Hayami method. Based on the result of the research, it can be concluded that the production of Roa fish sauce at Sal-Han industry on April 2017 used 15 kg Roa fish produced 119.79 kg of Roa fish sauce and produced 726 bottles. The income from the sauce 5.411.460 with profit 41.837 or 93.35%. The added value of sauce production is influenced by the big of output, raw material price, and contribution of ather input.